Epidemiology of Scorpion Stings in Southern Iran (Area under the Coverage of Iranshahr University of Medical Sciences) between 2020 and 2022 - Khoubfekr, Hekmatollah; Reisizadeh , Sanaullah; Balouchi, Abbas; Faraji Shahrivar, Farzaneh (Shahroud Journal of Medical Sciences, 2026)
Background: Scorpion envenomation remains a major public health problem in tropical and subtropical regions, particularly in southern Iran. The southeastern provinces, including Sistan and Baluchestan, provide favorable ecological conditions for scorpion proliferation. This study aimed to describe the epidemiological characteristics and outcomes of scorpion sting cases recorded in the catchment area of Iranshahr University of Medical Sciences.Methods: A retrospective descriptive-analytical study was conducted on all medical records of scorpion sting cases registered in health centers and hospital emergency departments across 12 counties affiliated with Iranshahr University of Medical Sciences between March 21, 2020, and March 20, 2022. Data included demographics, occupation, residence, sting location, temporal distribution, treatment received, and clinical outcomes.Results: During the two-year period, 12,307 scorpion sting cases were recorded, with a period prevalence of 319 per 100,000 population. Females (56.2%) and housewives (40.2%) were disproportionately affected. Most cases occurred in rural areas (78.5%) and during summer months, peaking between 10 PM and 2 AM. The hands and feet were the most common sting sites (77.6%). Antivenom was administered in 88.5% of cases, and the case fatality rate was 0.2% (21 deaths). Mortality was significantly associated with delayed hospitalization and lack of timely antivenom administration.Conclusions: Scorpion stings represent a continuing health challenge in southeastern Iran, particularly among rural women. Strengthening preventive education, ensuring timely access to antivenom, and improving clinical management protocols are essential to reduce morbidity and mortality in this endemic region.